2021
DOI: 10.1021/acsomega.0c03826
|View full text |Cite
|
Sign up to set email alerts
|

Efficient One-Step Conversion of a Low-Grade Vegetable Oil to Biodiesel over a Zinc Carboxylate Metal–Organic Framework

Abstract: In this study, a metal–organic framework, namely, Zn3(BTC)2 (BTC = 1,3,5-benzenetricaboxylic acid), was solvothermally synthesized and employed as a catalyst for biodiesel production from degummed vegetable oil via a one-step transesterification and esterification reaction. The resulting Zn3(BTC)2 particles exhibit a well-defined triclinic structure with an average size of about 1.2 μm, high specific surface area of 1176 m2/g, and thermal stability up to 300 °C. The response surface methodology–Box–Behnken des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…76 Alternatively, unlike T. M. M. Marso's two-step reaction, another MOF, Zn 3 (BTC) 2 (BTC = 1,3,5-benzenetricaboxylic acid), was fabricated by Lunardi et al to prepare biodiesel from degummed palm oil (DPO) via one-step trans/esterification, and the highest FAME yield was 89.89% under the optimized reaction conditions. 77 It was reported that Zn 3 (BTC) 2 emerged as a triclinic structure, possessing a large specific surface (1176 m 2 g −1 ) and reasonable thermal stability (up to 300 °C), as well as a mass of macropores and mesopores, which made it available for macromolecular substrate contacting with the Lewis acid catalytic site (Zn 2+ ) and promoted mass transport. The proposed mechanism for one-step trans/esterification is shown in Fig.…”
Section: Pristine Mofs Catalystsmentioning
confidence: 99%
“…76 Alternatively, unlike T. M. M. Marso's two-step reaction, another MOF, Zn 3 (BTC) 2 (BTC = 1,3,5-benzenetricaboxylic acid), was fabricated by Lunardi et al to prepare biodiesel from degummed palm oil (DPO) via one-step trans/esterification, and the highest FAME yield was 89.89% under the optimized reaction conditions. 77 It was reported that Zn 3 (BTC) 2 emerged as a triclinic structure, possessing a large specific surface (1176 m 2 g −1 ) and reasonable thermal stability (up to 300 °C), as well as a mass of macropores and mesopores, which made it available for macromolecular substrate contacting with the Lewis acid catalytic site (Zn 2+ ) and promoted mass transport. The proposed mechanism for one-step trans/esterification is shown in Fig.…”
Section: Pristine Mofs Catalystsmentioning
confidence: 99%
“…Recently, Zn 3 (BTC) 2 MOF (BTC: 1,3,5-benzenetricarboxylate) was solvothermally synthesized and its catalytic performance was studied in the simultaneous transesterification and esterification of degummed palm oil (DPO) to FAME (biodiesel). [53] Zn 3 (BTC) 2 was first reported by Yaghi et al, consisting of zinc(II) ions coordinated to BTC ligand and water with an open-framework having voids that are decorated by coordinately unsaturated metal centers upon removal of water by heating. [54] The characterization of Zn 3 (BTC) 2 by Lunardi et al revealed the existence of a hierarchical macro/ microporous structure and abundant open metal sites which can behave as Lewis acids.…”
Section: Open Metal Sites As Intrinsic Active Sitesmentioning
confidence: 99%
“…b) Comparison of the TOF value and conversion yield of Zn 3 (BTC) 2with the above commented catalysts for the transesterification and esterification reactions. Reproduced with permission [53]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…Heterogeneous solid base catalysts usually provide higher rates compared with the acid counterparts under milder reaction conditions. However, they cannot be directly employed for oil having more than 2 wt% FFA due to side reactions, such as saponification and hydrolysis, and decrease both the catalyst activity and the ester yield 15 . Hence, solid acid catalysts are applied when dealing with low-quality or non-edible vegetable oils containing significant quantities of FFAs and water 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, they cannot be directly employed for oil having more than 2 wt% FFA due to side reactions, such as saponification and hydrolysis, and decrease both the catalyst activity and the ester yield 15 . Hence, solid acid catalysts are applied when dealing with low-quality or non-edible vegetable oils containing significant quantities of FFAs and water 15 . Molybdenum compounds have been recognized as versatile catalysts, because of the ability of this metal to be on the solid surface in different oxidation states, ranging from Mo 6+ to metallic Mo (Mo 0 ) 16 .…”
Section: Introductionmentioning
confidence: 99%